Seroprevalence of helicobacter hepaticus in mice from laboratary animal facilities in Klang Valley, Malaysia - Che Lem, Siti Zubaidah; Hussein, Fuzina Nor; Mutalib, Abdul Rahim (2011)
Helicobacter is a genus of Gram-negativebacteria possessing a characteristic helix shape. They were initially considered to be members of the Campylobacter genus, but since 1989 they have been grouped in their own genus. Helicobacter hepaticusis an enterohepatic Helicobacter species (EHS) belonging to the family Helicobacteriaceae of the order Campylobacterales of Epsilon-proteobacteria division. It is a Gram-negative, microaerophilic, urease-positive, spiral rod. H. hepaticus colonises the colon and invades the liver of mice causing chronic severe active hepatitis and proliferative typhlocolitis. It can also induce hepatocellular carcinomas in certain breeds. The bacterium has been associated with inflammatory bowel disease in immunocompromised mice. Certain strains of mice will develop a proliferative, inflammatory typhlitis and/or colitis that may result in rectal prolapse. Detection of H. hepaticus in laboratory mice is therefore important because of its effect on research animals ultimately complicating the research findings. Currently PCR, culture, serology test or histologic examination of silver-stained liver sections is used to diagnose H. hepaticus infection. Most mice colonised with helicobacters remain asymptomatic for long periods of time. This study was conducted to investigate the serological prevalence of Helicobacter hepaticus in mice in 5 laboratory facilities in the Klang Valley. Fifty sera were collected and examined for presence of H. hepaticus antibodies by commercial ELISA test kit. Result showed two facilities had positive sera towards H. hepaticus while the rest were negative. Four of fifty sera were positive while other serum samples were negative.